Peculiarities of the course of chicken pox in children at the present stage - Nezgoda, Iryna; Levytska, Lidiia; Bobruk, Svitlana (Journal of Education, Health and Sport, 2018)
The article presents the results of a clinical and laboratory examination of 57 children suffering from chicken pox from 1 month to 16 years of age who were treated at the Vinnytsiya Regional Pediatric Clinical Infectious Disease Hospital from January to December 2017. Among the children who were included in the monitoring group, the overwhelming majority included patients aged 4 to 8 years (56.2%). The most difficult case was the disease in children under 4 years of age, which was due to the addition of complications, mainly because of central nervous system. Laboratory diagnostic methods have proved the viral etiology of the disease, in particular, all the examined children have been allocated Varicella Zoster Virus (VZV) by the immunoassay (ELISA) and polymerase chain reaction (PCR). A combination of VZV infection with an active form of another herpetic infection (EBV, CMV or HHV 6) was observed in 17 children (29.8%).